Optimization of Timing and Follow-Through Principles in Animal Motion Design: A 3D Approach for the Educational Game 'Suaka Satwa' - Juyendra, Atifa Syalsabilla; Geovanne Farell; Sheanny Ocmi Sakti; Wiki Lofandri (The Future of Education Journal, 2025)
This study optimizes the principles of timing and follow-through in 3D animation for the educational game "Suaka Satwa", which aims to introduce seven rare Indonesian animals to children aged 5–10. Using a Design Thinking approach, the study employs digital observation and literature review to identify the natural movement characteristics of each animal. The implementation of Inverse Kinematics (IK) and Forward Kinematics (FK) techniques was carried out to create realistic animations for idle, walking, and feeding movements. The results show a significant correlation between the animal's body size and the application of timing, as well as the effectiveness of follow-through in flexible body parts such as tails, trunks, and fins. The evaluation indicates that natural animation significantly contributes to the game's educational value by creating realistic and engaging visual representations. This research enhances animation standards in educational game development and offers an innovative approach to wildlife education.